THE ABYSS AND OTHER STORIES - Andreyev, Leonid, 1871-1919, |; Aplin, Hugh A. (London : Alma Classics, 2018)
As the young Zinaida and her sweetheart, the student Nemovetsky, stroll through the idyllic Russian countryside, their memories, dreams and thoughts about life and the future mingle in the evening breeze. But when night falls, they hasten to retrace their steps back to town through a small wood, where they are accosted by three threatening drunkards, who knock Nemovetsky unconscious and start to chase the girl through the underwood. When the young student comes round, he is confronted with the horror of what has just happened. Haunting, disquieting, shocking, 'The Abyss' -- one of the most powerful short stories ever written -- is accompanied in this volume by fifteen other stories, including 'Silence', 'The Thief' and 'Lazarus, some of them never translated before into English. Together, they provide a clear account of the lasting legacy of Russia's foremost man of letters of the early twentieth century.
Translated from the Russian.
Keywords: Andreyev, Leonid, -- 1871-1919 -- Translations into English; Short stories, Russian -- Translations into English